The Representation of Counterproductive Religious Values in a Selected Chapter of an Indonesian ELT Textbook: Systemic Functional Multimodal Discourse Analysis - Andriani, Agis; Abdullah, Fuad; Nurhaedin, Enjang; Hidayati, Arini Nurul; Rosmala, Dewi; Saputra, Yuyus (Journal of Pragmatics and Discourse Research, 2024)
Countless studies have examined the vital role of ELT textbooks as learning sources, particularly in terms of intercultural, multicultural, and trans-cultural analysis. Yet, none of them specifically talked about religious values as the research focus. Hence, this study aimed at construing religious values represented in a selected chapter of an Indonesian ELT textbook. Descriptive problem-driven content analysis was used as the research design, whilst the research data were collected through document analysis. Later, to analyze the data, the research utilized Systemic Functional Multimodal Discourse Analysis (SF-MDA) (O’Halloran, 2008c) as the framework with a focus on representational meaning and transitivity analysis for each visual and textual data. The findings showed that two data modes represent religiosity, namely visual and verbal data. In visual, religious values (artifacts, beliefs, and behaviors) are represented by the classificational process while in verbal data; they are represented by the material and relational processes. Four of Indonesia's large recognized religious communities were represented namely Christianity, Buddhism, Hinduism, and Confucianism. Yet, there is no single datum that figures Islamic values, whereas, the Islamic community is the largest in the country and even in the world. Hence, this implication suggests that stakeholders (particularly textbook authors) should pay attention to the issue of how to fairly present the five legalized communities' values existing in Indonesia. Therefore, because Indonesia has varied its communities, ethnicities, and backgrounds, ELT textbooks should fairly embody the diversities more over the religious aspects which are the core competence to gain.